ОRGANIZATIONAL AND METHODOLOGICAL ASPECTS OF THE CENTERS OF PERSONAL DEVELOPMENT OF CHILDREN IN THE SYSTEM OF PRESCHOOL EDUCATION - Kyrsta, Nataliia; Skomorovska, Iryna (Mountain School of Ukrainian Carpaty, 2022)
Modern development of science, technology and information technology expands the goals of child development, determines new needs and demands to the institutions of education and upbringing, in particular, preschool education. The need for innovation, transformation for improvement in the field of educational services requires clear theoretical justifications for the formation of new approaches, selection of methods and techniques of pedagogical influence, ways of their practical implementation. The factors that contribute to the spread and determine the need for the functioning of child development centers, among them, are: the emergence of new educational needs and the formation of alternative approaches to learning and education; mobility to transformations in the labor market; Deepening the understanding of the psychological features of childhood, sensitive periods, tumors, features of the cognitive and emotional spheres in a certain period. Such types of alternative education as home schooling, alternative schools, distance education, children's development centers are characterized. The advantages and disadvantages of each of them are revealed. The principles of activity of child development centers are analyzed as follows: personality-oriented approach in working with children and families, relying on the data of sociopedagogical diagnostics; principle of development; the principle of an open system, possibilities of regulation and choice in the process of pedagogical activity; the principle of interaction with the family and individual approach to the needs of the family; the principle of professional interaction (joint work with psychologists, teachers, speech pathologists, doctors). Keywords: preschool education, educational environment, centers of personal development of children, preschool children.